Teen Driver Distractions and Parental Norms. Issue 10 (October 2022) - Hoseinzadeh Nooshabadi, Mehdi; Vasquez, Holland; Merrikhpour, Maryam; Donmez, Birsen
Research related to parental norms on teen driver distractions is limited, although distracted driving is a serious concern for teens. This paper investigates whether teens' perception of their parent's engagement in and approval of distractions is different to what their parent reports, and whether any discrepancy relates to teens' self-reported distraction engagement frequency. It also investigates whether there are discrepancies between the parents' perception of their teen's distraction engagement frequency and the teen's self-report. A distinction is made between legal and illegal distractions as drivers may build stronger norms around illegal distractions. Analyses were conducted on data from 63 teen–parent dyads from Ontario, Canada, who completed an online survey, including self-reported engagement in 16 distractions and related descriptive (what parents/teens do) and injunctive (what parents approve/disapprove) norms. Dyads were divided into two groups: higher-engagers (n = 27) and lower-engagers (n = 36) based on teens' self-reported engagement frequency. Higher-engagers reported engaging in both distraction types (legal and illegal) more often than their parent did; there was no difference between lower-engagers and their parent. Higher-engagers' perception of their parent's engagement in and approval of legal distractions was higher than their parent's self-report, while these parents perceived their teen's engagement in both distraction types to be lower compared with the teen's self-report. The only discrepancy observed for lower-engagers was that teens' perception of their parent's approval of legal distractions was higher than parents' self-reports. Our findings suggest that misperceptions may exist for teens who engage more frequently in distractions and for their parents, who may benefit from relevant interventions.